Analisis pengaruh utang pemerintah terhadap perkembangan nilai tukar Negara Oman - Hana Saidah; Agustina Wiguna; Cindy Salsabila Putri; Endang Rostiana (Jurnal Riset Ilmu Ekonomi, 2021)
The Oman Rial is the currency with the third highest exchange rate in the world. 1 Oman Rial - US$2.6 . The exchange rate against the Omani USD was reported at 0.385 OMR/USD. With Oman's currency high, the government and the country's principal bank had to issue banknotes in denominations of 1/4 and 1/2 rials to accommodate transactions of small value. This examine study aims to analyze the factors that impact the movement of the Oman riyal exchange rate, using secondary facts data sourced from the World Bank and IMF in 1984-2019. Data analysis using multiple linear regression through the Eviews application. From the analysis, it is known that interest rate, term of trade, public debt, and reserves affect the exchange rate. Interest rate, term of trade, and public debt have a negative effect on the exchange rate with a regression coefficient of -0.000295 , -0.008934 , and -0.000164, respectively. Reserves have a positive effect on the exchange rate with a coefficient of 2.13. The variables that have a very large influence on the exchange rate are reserves.